Original paperThe role of focal infections in the pathogenesis of psoriasis and chronic urticaria - Brzewski, Paweł Łukasz; Spałkowska, Magdalena; Podbielska, Magdalena; Chmielewska, Joanna; Wołek, Marta; Malec, Katarzyna; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : The Focal Infection Theory, originally presented at the beginning of the 20th century, postulates that systemic diseases can be caused by microorganisms that arise from the focus of infection. Foci of infections have been described as sinuses, adenoids, tonsils, teeth, genitourinary tract, gall bladder and kidneys. A focus of infection is defined as the area that can occur in any part of the body, contains a pathogen (microorganism) and is usually asymptomatic. There are discordant opinions about the role of focal infections in the pathogenesis of psoriasis and urticaria. Aim : To establish whether there is a higher incidence of focal infections in patients with chronic urticaria and psoriasis. Material and methods : We retrospectively reviewed 129 patients with a history of psoriasis and chronic urticaria: 58 women and 71 men treated in the Department of Dermatology of the Jagiellonian University Medical College in Krakow. Results: In the analyzed group, 11 patients had a dental consultation, 58 – laryngological consultation and 29 women had a gynecological consultation. The most common examples of focal infection were tonsillitis, upper respiratory tract infections, sinusitis, dental caries and genitourinary tract infections. Aggravating factors were similar to previously described. Conclusions : A high incidence of focal infections in patients with psoriasis and urticaria suggests that infections may play a significant role in the pathogenesis of these skin disorders. Treatment of infection foci may play the key role in the remission of skin changes. Key words: focal infection, urticaria, psoriasis.